2021
DOI: 10.1101/2021.08.12.456045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy cargo receptors are secreted via extracellular vesicles and particles in response to endolysosomal inhibition or impaired autophagosome maturation

Abstract: The endosome-lysosome (endolysosome) system plays central roles in both autophagic degradation and secretory pathways, including the exocytic release of extracellular vesicles and particles (EVPs). Although previous work has revealed important interconnections between autophagy and EVP-mediated secretion, our molecular understanding of these secretory events during endolysosome inhibition remains incomplete. Here, we delineate a secretory autophagy pathway upregulated in response to endolysosomal inhibition th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is also well known that ferritin is secreted, and this secretion is enhanced in some diseases, including hemophagocytic lymphohistiocytosis and adult-onset Still’s disease ( Rosario et al, 2013 ). NCOA4 and ferritin can be secreted via extracellular vesicles ( Solvik et al, 2021 ; Yanatori et al, 2021 ). Thus, ferritin–NCOA4 condensates may be directed to both lysosomal degradation and secretion after incorporation into endosomes.…”
Section: Resultsmentioning
confidence: 99%
“…It is also well known that ferritin is secreted, and this secretion is enhanced in some diseases, including hemophagocytic lymphohistiocytosis and adult-onset Still’s disease ( Rosario et al, 2013 ). NCOA4 and ferritin can be secreted via extracellular vesicles ( Solvik et al, 2021 ; Yanatori et al, 2021 ). Thus, ferritin–NCOA4 condensates may be directed to both lysosomal degradation and secretion after incorporation into endosomes.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that ferritin is secreted and this secretion is enhanced in some diseases, including hemophagocytic lymphohistiocytosis and adult-onset Still's disease (Rosario et al, 2013). Moreover, autophagy-related proteins such as NCOA4 were found to be secreted via extracellular vesicles (Solvik et al, 2021). Furthermore, a recent paper reported that ferritin secretion via extracellular vesicles depends on NCOA4 (Yanatori et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was noted that these extracellular vesicles can be efficiently processed for antigen presentation on MHC class I and II molecules (73,74). Inhibition of lysosomal acidification or of the fusion machinery between autophagosomes and lysosomes leads to the release of vesicles that contain autophagy receptors, such as p62 and NBR1 (75,76). These receptors recruit most likely ubiquitinated protein aggregates of both long-and short-lived proteins (71) into autophagosomes whose inner membrane is then released for unconventional secretion after autophagosome fusion with multivesicular bodies (MVBs) and successive exocytosis from MVBs.…”
Section: Antigen Secretion With the Assistance Of The Macroautophagy ...mentioning
confidence: 99%